EROS AND GROTESQUE IN LAUGHABLE LOVES BY MILAN KUNDERA - Baricevic, Luka (Bohemica Olomucensia, 2021)
The aim of this paper is to recognize and explain grotesque elements in Laughable Loves by Milan Kundera, where I try to elucidate what constitutes the grotesque and all the ways it manifests in Kundera's book. In addition, I suggest that in the given collection of short-stories two main types of grotesque can be found and thoroughly elaborate them.
Keywords: Milan Kundera; Laughable Loves; grotesque; Don Juan